EEGLAB, SIFT, NFT, BCILAB, and ERICA: New Tools for Advanced EEG Processing - Mullen, Tim; Akalin Acar, Zeynep; Delorme, Arnaud; Makeig, Scott; Vankov, Andrey; Bigdely-Shamlo, Nima; Kothe, Christian (Computational Intelligence and Neuroscience, 2011)
We describe a set of complementary EEG data collection and processing tools recently developed at the Swartz Center for Computational Neuroscience (SCCN) that connect to and extend the EEGLAB software environment, a freely available and readily extensible processing environment running under Matlab. The new tools include (1) a new and flexible EEGLAB STUDY design facility for framing and performing statistical analyses on data from multiple subjects; (2) a neuroelectromagnetic forward head modeling toolbox (NFT) for building realistic electrical head models from available data; (3) a source information flow toolbox (SIFT) for modeling ongoing or event-related effective connectivity between cortical areas; (4) a BCILAB toolbox for building online brain-computer interface (BCI) models from available data, and (5) an experimental real-time interactive control and analysis (ERICA) environment for real-time production and coordination of interactive, multimodal experiments.